Employment regulation and productivity: Is there a case for deregulation? - Michael Brookes; Philip James; Marian Rizov (Economic and Industrial Democracy, 2016)
This paper explores empirically the economic validity of the relatively limited approach to the regulation of employment protection pursued in the UK over the last three decades and within the European Union more recently. It does so by comparing the UK's manufacturing labour productivity performance with those of three countries – France, Germany and Sweden – that possess more stringent employment protection laws. The findings reveal that while productivity growth in the UK was superior to France and Sweden, it was lower than in Germany. More generally, the study's findings fail to support the existence of a straightforward negative relationship between regulatory stringency and productivity growth.
Keywords: J21; J38; J53; J83; J88; 330; Employment protection; labour productivity; legal regulation; Europe